Optimization of ultrasound-assisted extraction of total flavonoids content from the white flowering variety of Melastoma Malabathricum - Lee, Chia Hau; Lee, Ting Hun; Harisun Ya’akob; Wong, Syieluing; Jannet, Hichem Ben (Penerbit Universiti Kebangsaan Malaysia, 2019)
Melastoma malabathricum or Senduduk Putih is one of the herbs listed under National Key Economic Area (NKEA) of Malaysia. It has the potential to be used as remedies that is rich in natural flavonoids. One of the innovations for extraction in modern technology is Ultrasound-Assisted Extraction (UAE) that showed several advantages. Therefore, this study aimed to explore using UAE to extract the total flavonoids in M. malabathricum. After that, UAE is optimized coupled with a stirrer for total flavonoid extraction. Five operating parameters: ethanol concentration, plant material to solvent ratio, extraction temperature, extraction time and ultrasound power were investigated by one-factor-at-a-time (OFAT) method to choose the most important parameters. After that, the response surface methodology coupled with face-centered central composite design (FCCD) was employed to study the interaction of the three keys parameters. The optimized conditions to extract total flavonoids content by UAE with constant mixing speed (300 ± 6 rpm) were at a ratio of 1g of plant material: 30 mL of 100% (v/v) ethanol, extraction temperature at 70oC, 19 min of extraction time and 280 W of ultrasound power. The experimental yields of total flavonoids content were 64.94 mg/g, which is well matched with the predicted value of 63.75 mg/g.